Penerapan Continuity Editing dalam Konstruksi Naratif Film Kucumbu Tubuh Indahku - Muhammad Muttaqien; Nurhadiatama, Desta Arya (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the application of continuity editing in the film Kucumbu Tubuh Indahku and its role in building the film's narrative structure. The primary objective of this study is to analyze the editing techniques used and identify the editor's contribution to shaping the visual storytelling. The method used is descriptive qualitative, with primary data collected through interviews with the film editor and observations of the film itself. The results of the study indicate that continuity editing functions to maintain narrative continuity and the emotional flow that develops throughout the story. The editing techniques used in this film include cut-in, match on action, and eyeline match, all of which work to create smooth transitions between different scenes. The cutting points in the film become key elements in regulating the rhythm, visual emphasis, and dramatic intensity within the storyline. Each decision regarding the cutting point made by the editor can produce different emotional effects, which directly influence the pacing and dynamics of the story. This study emphasizes that careful editing decisions are crucial in strengthening the visual and dramatic aspects of the film and help build a strong narrative experience for the audience.